(untitled) (Jurnal Online Pertanian Tropik, 2019)
Effect of immersion duration of trichoderma harzianum on local chili growth the aim of this research is to see the old soaking ability of Trichoderma harzianum mushroom on the growth of local chili. The design used was a Completely Randomized Design (CRD) consisting of 6 treatments and 4 replications, namely local chili seeds soaked with a 5-minute T.harzianum suspension, local chili seeds soaked with a 10-minute T.harzianum suspension, local chili seeds that were soaked marinated with T.harzianum suspension for 15 minutes, local chili seeds soaked with T.harzianum suspension for 20 minutes, local chili seeds soaked with T.harzianum suspension for 25 minutes, Control (without immersion with trichoderma harzianum suspension. Observed parameters are the percentage of local chili growth, plant height and number of leaves The results showed that the application of trichoderma harzianum had a good effect on the growth of chili plants, soaking for 25 minutes was the best soaking on local chili seeds.